Post-exercise skimmed milk, but not a sucrose beverage decreases energy intake at the next meal compared to a placebo beverage in active males. (1st February 2023) - Corney, R.A.; Clayton, D.J.; Nash, J.; Joel, T.; Sunderland, C.; James, L.J.
Abstract: This study compared the appetite and energy intake effects of three post-exercise beverages at a subsequent post-exercise meal. On three occasions, ten active males: (mean ± sd) age 21.3 ± 1.2 y, V ˙ O2 peak 58 ± 5 mL/kg/min) performed 30-min cycling at ∼60% V ˙ O2 peak and five 4-min intervals at 85% V ˙ O2 peak. Post-exercise, placebo (PLA: 57 kJ), skimmed milk (MILK: 1002 kJ) or sucrose (CHO: 1000 kJ) beverages (615 mL) were consumed. Sixty min post-beverage, subjects consumed an ad-libitum pasta lunch in a 30 min eating period. Subjective appetite and plasma acylated ghrelin and plasma glucose were determined pre-exercise, post-exercise and pre-meal, with sensory characteristics of beverages rated. Ad-libitum energy intake in MILK (6746 ± 2035) kJ) was lower than CHO (7762 ± 1921) kJ) ( P = 0.038; dz = 0.98; large effect) and tended to be lower than PLA (7672 (2005) kJ) ( P = 0.078; dz = 0.76; medium effect). Including energy consumed in beverages, energy intake was greater in CHO than PLA ( P  = 0.010; dz = 1.24; large effect) or MILK ( P  = 0.026; dz = 0.98; large effect), with PLA and MILK not different ( P = 0.960; dz = 0.02; trial effect). Plasma ghrelin, plasma glucose and appetite were not different between trials. MILK was perceived thicker than CHO ( P  = 0.020; dz = 1.11; large effect) and creamier than PLA ( P  = 0.026; dz = 1.06; large effect). These results suggest that when energy balance is important for an exerciser, post-exercise skimmed milk ingestion reduces energy intake compared to a sucrose beverage and might therefore help facilitate recovery/adaptation without affecting energy balance.